The Intention to Pay Zakat Commercial: An Application of Revised Theory of Planned Behavior - Heikal, Mohd; ., Falahuddin (Journal of Economics and Behavioral Studies, 2014)
Several researches have been carried out to predict the intention to pay zakat using the factors introduced by the Theory of Planned Behavior – developed by Ajzen & Fishbein (1980). Meanwhile, an addition of predicting past behavior factor on the intention to pay zakat has not been found in previous researches. The purpose of this research is to analyze the influence of attitude, subjective norms, perceived behavioral control and past behavior towards the intention of traders in the Lhokseumawe city to pay zakat commercial. The revised Theory of Planned Behavior was used in the research. This study aims to predict the intention of zakat payers. A total of 2,432 traders as the population of the research was identified and 150 of them were chosen as respondents determined using the purposive sampling technique. Using multiple linear regression models, it has found that the subjective norms, perceived behavioral control and past behavior partially have positive and significant influence towards the intention to pay zakat commercial. It also finds that past behavior variable has the most dominant impact towards the intention of zakat payers, while attitude has the least impact towards the intention. Finally, there is a simultaneously positive and significant influence towards the intention to pay zakat commercial.